KINERJA PORTOFOLIO SAHAM INFRASTRUKTUR, KEUANGAN DAN KONSUMSI BERDASARKAN STRATEGI INVESTASI SEKTORAL DI PASAR MODAL INDONESIA - Luh Made Ariesty Paskawati (STIMI Handayani Denpasar, 2013)
Portfolio diversification which aims to minimize the risk is conducted by a combinationsectoral of shares forming portofolios.The population of this study was stocks listed in the infrastructure sector, financeand consumption in the year 2008 and 2011. Analysis in this study is by Single IndexModel. The measurement of portfolio performances using Sharpe, Treynor andJensen index.Portfolio performance of each sector in 2008 was found as measured by theSharpe, Treynor index was not significantly different to the index while for Jensenwas not significantly different in infrastructure-finance and finance-consumption.Optimal portfolio performance of two sectors combination measured by all indexwas significantly not different while the performance of the portfolio while theperformance of the portfolioof each sector, two and three sectors combination did notdiffer significantly in the Sharpe and Treynor index while in Jensen it was not differsignificantly in financial with financial-infrastructre, financial with infrastructureconsumption,financial with financial-consumption, financial with infrastructurefinancial-consumption.Optimal portfolio performance in 2011 in each sectors, thecombination of two sectors and the combination betweeen each sectors, combinationof two and three sectors was not significantly different in that index.It is suggested that investor to consider the characteristics of the sector and adaptedto market conditions and the economy.